2018
DOI: 10.1186/s12961-018-0315-z
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the concept and importance of the health research system in Palestine: a qualitative study

Abstract: BackgroundThe importance of a health research system (HRS), namely an instrument for developing and enabling health systems, is increasing, particularly in developing countries. Assessing the perceptions of system performers is a necessary part of system analysis, which seeks to recognize a system’s strengths and limitations aiming towards improvement. This study assesses the perceptions of policy-makers, academicians and experts regarding the HRS concept and its importance to generate insights for system stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 25 publications
2
26
0
Order By: Relevance
“…These frameworks serve as a basis for understanding HSs through a wide-range analysis [11][12][13] and strengthening these capacities from a system-wide approach, as other similar studies showed [14][15][16][17]. Evaluating and strengthening the capacities of a HRS is essential to improve health outcomes and address global health challenges not only in developing countries but also worldwide [14,18].…”
Section: Introductionmentioning
confidence: 94%
“…These frameworks serve as a basis for understanding HSs through a wide-range analysis [11][12][13] and strengthening these capacities from a system-wide approach, as other similar studies showed [14][15][16][17]. Evaluating and strengthening the capacities of a HRS is essential to improve health outcomes and address global health challenges not only in developing countries but also worldwide [14,18].…”
Section: Introductionmentioning
confidence: 94%
“…The responses covered the findings in three key areas. Apart from the socio-demographic characteristics of the participants that were previously presented in other relevant published (7)(8)(9) and in press studies, two other areas were as follows: 1) the overall existing situation, limiting, and facilitating factors of human resources, infrastructure, and facilities of the HRS; and 2)The scene of HRS financing, sources, gaps, and best solutions for optimization. HRS human resources and infrastructure and HR financing are the main two findings that the current study focuses on.…”
Section: Resultsmentioning
confidence: 99%
“…Perceptions of participants from three sectors in Palestine -the government, academia, and local and international Non-governmental organizations (NGOs) -were investigated. The approaches of collecting, managing, and analysing data through conducting 52 in-depth interviews (IDIs) and 6 focus group discussions (FGDs) were also typically adopted and used in previous similar studies in Palestine (7)(8)(9).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study targeted a diverse group of stakeholders including experts, policy-makers, academics, and directors from the three relevant Palestinian sectors: government, academia, and local and international non-governmental organizations (NGOs). The methods of data collection, management and analysis were similar to other national studies (18,19). Data were collected through 52 in-depth interviews (IDIs) and 6 focus group discussions (FGDs) and then analysed using MAXQDA 12 software (VERBI GmbH, Berlin, Germany).…”
Section: Methodsmentioning
confidence: 99%